Kinematic analysis of swimming relay starts with the Omega OSB11 starting-block - Qiu, X.; Minarro, F.; Navarro, E.; Veiga, S. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: In competitive elite swimming, we can observe different types of relay starts like starts with parallel feet, starts with separated feet and starts with steps. It is unknown what of these starts is the fastest for a better performance. Therefore, the purpose of the present study was to examine the effect of a previous step In the different variables (kinematics, performance, temporal, spatial and angular) of the relay starts using the dispositive Omega OSB11. Methods: The swimmers performed 3 types of relay starts (non step start with parallel feet, separated start and one step start) randomly, with maximum effort, to 25m with rest between each. Three fixed cameras were used to tape all the videos, at 100 Hz. In each of the swimmers footage, twenty-one body landmarks were manually digitized to define fourteen segments according to the Zatsiorsky-Seluyanov model, modified by De Leva. The real coordinates were reconstructed from the screen coordinated by 2D direct linear transformation (2D-DLT) based algorithms. Magnitude-based inference was used to evaluate the reliability of the digitalization and to verify the differences In the lineal and angular kinematic variables of the three relay starts. Results: The time at 5m with separated start was faster than other two types starts (2.55±0.44). And the time of underwater was better with parallel feet (83.05±3.20) while separated start was the greatest at the change time (4.68±3.68). The take-off height, entry height, Immersion velocity at Yaxis and take-off angle were greater with separated start (1.25±0.07, 0.62±0.07, -2.05±0.49,186.06±5.71). There were better performances in the entry velocity at X axis and immersion angle with parallel feet (3.99±0.65, 331.42±5.16), and in the initial distance with one step start (0.34±0.04). Conclusion: There have been a few studies on relay starts. The previous studies reported the non step start is better for achieving consistent and superior performance and the horizontal velocity generated by legs driving was significantly greater than that In step start. Our study identified that many variables of the separated start were greater than that behaved by non step start with parallel feet and one step start. Therefore, the separated start may help swimmers perform better in relay events.